Pulmonary artery stump thrombosis developed during the late postoperative period - Akcam, Tevfik Ilker; Kaya, Seyda Ors; Samancilar, Ozgur; Ceylan, Kenan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
A 73-year-old man underwent left pneumonectomy for squamous cell lung carcinoma 3 years ago. The postoperative and follow-up periods were uneventful. A thrombus was detected in the left pulmonary artery stump during the last chest computed tomography (CT) scan. Anticoagulant treatment was applied: intravenous heparin for 3 days followed by oral warfarin. The follow-up chest CT examination revealed regression in the size of the thrombus.